2015
DOI: 10.1186/s12888-015-0585-8
|View full text |Cite
|
Sign up to set email alerts
|

Indoor rock climbing (bouldering) as a new treatment for depression: study design of a waitlist-controlled randomized group pilot study and the first results

Abstract: BackgroundDepression is one of the most common diseases in industrialised nations. Physical activity is regarded as an important part of therapeutic intervention. Rock climbing or bouldering (rock climbing to moderate heights without rope) comprises many aspects that are considered useful, but until now, there has been hardly any research on the effects of a bouldering group intervention on people with depression. The purpose of this controlled pilot study was twofold: first, to develop a manual for an eight-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
121
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(141 citation statements)
references
References 35 publications
(29 reference statements)
11
121
0
9
Order By: Relevance
“…A full concentration, which is needed to a successful ascent, can generate a https: //dx.doi.org/10.15405/epsbs.2019.02.02.14 Corresponding Author: Dagmar Hrušová Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 2357-1330 125 very intensive experience and allows a climber to "be here now". This is in agreement with Luttenberger et al (2015) and the suggested difference of climbing from other common sports, in terms of supporting not only physical but also cognitive and emotional resources.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A full concentration, which is needed to a successful ascent, can generate a https: //dx.doi.org/10.15405/epsbs.2019.02.02.14 Corresponding Author: Dagmar Hrušová Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 2357-1330 125 very intensive experience and allows a climber to "be here now". This is in agreement with Luttenberger et al (2015) and the suggested difference of climbing from other common sports, in terms of supporting not only physical but also cognitive and emotional resources.…”
Section: Discussionsupporting
confidence: 92%
“…Thus a full concentration can generate a very intensive experience and allows a climber to "be here now". In addition, there are emotions in climbing linked to the present moment, such as fear, pride, and trust (Luttenberger et al, 2015). Killingsworth and Gilbert (2010) pointed out that happiness is to be found by living in the moment, and people should train to resist mind wandering and to "be here now", in harmony with philosophical and religious traditions.…”
Section: Experiencing and Psychological Involvement In Sport Climbingmentioning
confidence: 99%
“…Wie bewerte ich einen Erfolg?) Viele Teilnehmer unserer erapiegruppen [23] berichten nach der erapie, dass sie sich bei Problemen im Leben nun häu g fragen "Wie hätte ich es beim Bouldern gemacht? "…”
Section: Transfermöglichkeitenunclassified
“…Das stärkt massiv das Selbstwirksamkeitsemp nden. So konnten wir nach einer achtwöchigen Bouldertherapie in der Interventionsgruppe eine Verbesserung des Selbstwirksamkeitsemp ndens und der Copingstrategien beobachten, wäh-rend diese in der Wartegruppe unverän-dert blieben [23].…”
Section: Selbstwirksamkeitunclassified
See 1 more Smart Citation